2021
DOI: 10.1055/s-0040-1706658
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Regioselective Synthesis of Isomeric 3-[Isoxazol-3(or 5)-yl]indoles from β-Ethylthio-β-indolyl-α,β-unsaturated Ketones

Abstract: A simple and efficient method for the complementary and regioselective synthesis of isomeric 3-(isoxazol-5-yl)indoles and 3-(isoxazol-3-yl)indoles has been developed by the regioselective cyclocondensation reaction of β-ethylthio-β-indolyl-α,β-unsaturated ketones and hydroxylamine hydrochloride. It was found that the cyclocondensation reaction in the presence of excess NaOEt in refluxing EtOH gives 3-(isoxazol-5-yl)indoles in good yields, whereas using NaOAc in boiling AcOH gives 3-(isoxazol-3-yl)indoles in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A variety of N-unsubstituted pyrazoles bearing indole units have been synthesized from the cyclocondensation reaction of β-ethyltho-β-indolyl-α, β-unsaturated ketones and hydrazine hydrate or semicarbazide hydrochlorides as a hydrazine equivalent in organic solvent or water [31][32][33]. Furthermore, by controlling the reaction conditions, the regioselective synthesis of isomeric 3-(1-substituted pyrazol-3(5)yl) indoles was also successfully realized when βethyltho-β-indolyl-α, β-unsaturated ketones reacted with monosubstituted hydrazines [34]. Subsequently, we developed the Ag 2 CO 3 -catalyzed aza-Michael addition of pyrazoles to α, βunsaturated carbonyl compounds, to afford a series of N-alkylated pyrazoles in excellent yields and with high regioselectivity [35].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of N-unsubstituted pyrazoles bearing indole units have been synthesized from the cyclocondensation reaction of β-ethyltho-β-indolyl-α, β-unsaturated ketones and hydrazine hydrate or semicarbazide hydrochlorides as a hydrazine equivalent in organic solvent or water [31][32][33]. Furthermore, by controlling the reaction conditions, the regioselective synthesis of isomeric 3-(1-substituted pyrazol-3(5)yl) indoles was also successfully realized when βethyltho-β-indolyl-α, β-unsaturated ketones reacted with monosubstituted hydrazines [34]. Subsequently, we developed the Ag 2 CO 3 -catalyzed aza-Michael addition of pyrazoles to α, βunsaturated carbonyl compounds, to afford a series of N-alkylated pyrazoles in excellent yields and with high regioselectivity [35].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the importance of ortho -acylphenols and our ongoing interests in aqueous organic synthesis and the synthetic application of α-oxo ketene dithioacetals, we recently researched in detail tandem [5C + 1C] annulations of α-alkenoyl ketene dithioacetals and nitroethane in water to prepare ortho -acylphenols. It was found that there were tandem Michael addition/cyclization/aromatization reactions between α-alkenoyl ketene dithioacetals and nitroethane in the presence of 2.0 equivalents of DBU in boiling water, affording ortho -acylphenols in excellent yields (Scheme ).…”
Section: Introductionmentioning
confidence: 99%